Comparative Study of the Measurement of Enamel Demineralization and Remineralization Using Transverse Microradiography and Electron Probe Microanalysis. (24th April 2014) - Cochrane, Nathan J.; Iijima, Youichi; Shen, Peiyan; Yuan, Yi; Walker, Glenn D.; Reynolds, Coralie; MacRae, Colin M.; Wilson, Nicholas C.; Adams, Geoffrey G.; Reynolds, Eric C.
Abstract Transverse microradiography (TMR) and electron probe microanalysis (EPMA) are commonly used for characterizing dental tissues. TMR utilizes an approximately monochromatic X-ray beam to determine the mass attenuation of the sample, which is converted to volume percent mineral (vol%min). An EPMA stimulates the emission of characteristic X-rays from a variable volume of sample (dependent on density) to provide compositional information. The aim of this study was to compare the assessment of sound, demineralized, and remineralized enamel using both techniques. Human enamel samples were demineralized and a part of each was subsequently remineralized. The same line profile through each demineralized lesion was analyzed using TMR and EPMA to determine vol%min and wt% elemental composition and atomic concentration ratio information, respectively. The vol%min and wt% values determined by each technique were significantly correlated but the absolute values were not similar. This was attributable to the complex ultrastructural composition, the variable density of the samples analyzed, and the nonlinear interaction of the EPMA-generated X-rays. EPMA remains an important technique for obtaining atomic ratio information, but its limitations in determining absolute mineral content indicate that it should not be used in place of TMR for determining the mineral density of dental hard tissues.